Walter Rosene daily journal, 1922 - Rosene, Walter M., Sr., 1880-1941et al
A diary from 1922 that Walter Rosene used to record bird sightings and weather conditions. Also included are mileage records from 1916-1922 and several addresses of Rosene's colleagues. Nikon--camera